The answer to this is x^2 + 2x - 5
Answer:
let the number be x
4x-6=3x+8
Step-by-step explanation:
hope this helps you
If yes then do mark my answer as brainliest
Answer:
- 2x² + 2x + 11
Step-by-step explanation:
Given
x² + 6 - (3x² - 2x - 5) ← distribute parenthesis by - 1
= x² + 6 - 3x² + 2x + 5 ← collect like terms
= - 2x² + 2x + 11
Answer:
StartFraction g Over 6 EndFraction = 16; g = 96
Step-by-step explanation:
The quotient of a number and six is sixteen.
A quotient is a result obtained by dividing one quantity by another.
Thus, we have g to be the unknown number = g / 6 = 16
Thus, g = 16*6 = 96.